2017
DOI: 10.5935/1806-6690.20170007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of land use/occupation on water quality in the Trussu river valley, Ceará, Brazil

Abstract: Influência do uso/ocupação da terra na qualidade das águas no vale do rio Trussu, Ceará, Brasil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Tal fato foi constatado também por Coelho et al (2014), onde ao estudar a dinâmica do uso e ocupação do solo na bacia hidrográfica do riacho São Paulo, localizada no semiárido brasileiro, foi elucidado que junto com o rápido crescimento das áreas de pastagem/agricultura, a vegetação nativa foi sendo substituída por uma paisagem cada vez mais devastada. No estudo realizado por Araújo Neto et al (2017), no vale do rio Trussu -Ceará, foi visto que as atividades antrópicas passaram a ocupar 40,7% da área estudada, gerando uma redução de 38,7% para 11,2% das áreas florestais para uso em atividades humanas como agricultura, pastoreio e urbanização.…”
Section: Resultsunclassified
“…Tal fato foi constatado também por Coelho et al (2014), onde ao estudar a dinâmica do uso e ocupação do solo na bacia hidrográfica do riacho São Paulo, localizada no semiárido brasileiro, foi elucidado que junto com o rápido crescimento das áreas de pastagem/agricultura, a vegetação nativa foi sendo substituída por uma paisagem cada vez mais devastada. No estudo realizado por Araújo Neto et al (2017), no vale do rio Trussu -Ceará, foi visto que as atividades antrópicas passaram a ocupar 40,7% da área estudada, gerando uma redução de 38,7% para 11,2% das áreas florestais para uso em atividades humanas como agricultura, pastoreio e urbanização.…”
Section: Resultsunclassified
“…Well 1, in turn, presented a positive relationship with the conductivity, hardness and pH parameters and the native vegetation. In comparison with literature data, Araújo Neto, Andrade, Palácio, Sales, and Maia (2017) studied the influence of the use and occupation of the soil on the water quality in the valley of Rio Trussu in Ceará State (Brazil), and found that over the last ten years the region under study has undergone major changes due to anthropogenic activity that directly affected the characteristics of the groundwater quality. They highlighted the importance of studies that relate the local characteristics with the quality of the water.…”
Section: Relation Of Use and Occupation Of The Soil With Water Qualitymentioning
confidence: 99%
“…The study of water quality in waterbodies is of fundamental importance to determine the health of the environment and consequently public health (MEDEIROS et al, 2016). In the semi-arid region of Brazil, such studies play a crucial role in guaranteeing economic and social development, since in this region water is a limiting resource due to its scarcity and intermittency throughout almost the entire hydrographic area (ARAÚJO NETO et al, 2017). It is therefore essential to monitor water quality, in order to prevent the scarce water sources of this region from becoming unusable.…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic ecosystems, the health of the environment can be inferred based on a characterisation of its structure (biological elements and their interaction with physical and chemical variables) and function (processes fundamental to maintaining biodiversity, such as the production, consumption and decomposition of organic matter) (ARAÚJO et al, 2011). As such, various studies have used remote sensing to quantify the effects that different land uses and temporal changes in the structure of the landscape have caused to the health of waterbodies (ARAÚJO NETO et al, 2017;CHAVES et al, 2019;MENEZES et al, 2016;VA N ZELA;HERNANDEZ;FRANCO, 2010).…”
Section: Introductionmentioning
confidence: 99%